Species limits and recent diversification of Cerradomys (Sigmodontinae: Oryzomyini) during the Pleistocene - Camilla B. Di-Nizo; Elkin Y. Suárez-Villota; Maria José J. Silva (PeerJ, 2022)
Cerradomys is a genus of the tribe Oryzomyini with eight species currently recognized, and a controversial taxonomy. These species are mainly distributed in the South America dry diagonal, but some species extend into Atlantic Forest, reaching the coastal sandy plains known as Restingas. This study aimed to address species limits and patterns of diversification of Cerradomys species. For this purpose, we performed cytogenetic and molecular analyses (phylogeny, coalescent species delimitation, barcoding, and divergence times estimation) using multiple mitochondrial and nuclear markers on a comprehensive sampling, representing all nominal taxa reported so far. Chromosomal information was a robust marker recognizing eight Cerradomys species. Reciprocal monophyly was recovered for all the species, except for C. subflavus. These results together with coalescent analyses recovered eight species as the most congruent species delimitation scenario for the genus (mean Ctax: 0.72). Divergence time estimates revealed that Cerradomys’ diversification occurred about 1.32 million years ago (Mya) during the Pleistocene. Although our results conservatively support the eight Cerradomys species described so far, different lines of evidence suggest that C. langguthi and C. subflavus could potentially be species-complexes. We discussed this scenario in the light of multiple evolutionary processes within and between species and populations, since Cerradomys comprises a species group with recent diversification affected by Pleistocene climatic changes and by the complex biogeographic history of South America dry diagonal. This work supports that the diversity of Cerradomys is underestimated and reiterates that interdisciplinary approaches are mandatory to identify small rodent species properly, and to unhide cryptic species.